Efficiency of the ecuadorian criminal law: economic analysis of misdemeanors - Cárdenas Vargas, Michelle Estefanía (2018)
This paper develops and indicates the economic analysis of criminal law, specifically misdemeanors in Ecuador. It focuses on a theoretical study of the circumstances that motivate the offender to commit unlawful acts and incur the commission of minor offenses, the penalties referred to as a sanction for these acts and the cost to the state. The document is focus on a study of law based on microeconomics science to indicate the responsibility of the subject who commits minor offenses, how the country responses to these actions and the way it tries to avoid offenses improving public policies. KEYWORDS: criminal law, minor offences, contraventions, cost-benefit, incentives. JEL CODE: D61, G14